2022
DOI: 10.1158/1078-0432.ccr-22-2533
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Copy Number and Resistance Mechanisms in Patients with HER2-positive Advanced Gastric Cancer Receiving Initial Trastuzumab-based Therapy in JACOB Trial

Abstract: Purpose: In JACOB trial, pertuzumab added to trastuzumab-chemotherapy did not significantly improve survival of patients with HER2-positive metastatic gastric cancer, despite 3.3 months increase versus placebo. HER2 copy number variation (CNV) and AMNESIA panel encompassing primary resistance alterations (KRAS/PIK3CA/MET mutations, KRAS/EGFR/MET amplifications) may improve patients’ selection for HER2 inhibition. Experimental design: In a post-hoc analysis of JACOB on 327 samples successfully sequenced by NGS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…However, the optimal cut-off value of ERBB2 CNA for predicting prognosis in patients receiving trastuzumab therapy remains undetermined. Previous studies have demonstrated that elevated continuous copy numbers of ERBB2 correlate significantly with extended PFS [ 25 , 26 ], and higher cut-off values of ERBB2 CNA, compared to those employed in the current study, have proven advantageous for prognostic categorization in patients undergoing trastuzumab therapy [ 26 , 27 ]. Further exploration aimed at delineating the optimal cut-off values capable of predicting the efficacy of trastuzumab therapy specifically in patients with GC will advance anti-HER2 therapy for unresectable metastatic disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the optimal cut-off value of ERBB2 CNA for predicting prognosis in patients receiving trastuzumab therapy remains undetermined. Previous studies have demonstrated that elevated continuous copy numbers of ERBB2 correlate significantly with extended PFS [ 25 , 26 ], and higher cut-off values of ERBB2 CNA, compared to those employed in the current study, have proven advantageous for prognostic categorization in patients undergoing trastuzumab therapy [ 26 , 27 ]. Further exploration aimed at delineating the optimal cut-off values capable of predicting the efficacy of trastuzumab therapy specifically in patients with GC will advance anti-HER2 therapy for unresectable metastatic disease.…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, compared with no ERBB2 AMP, ERBB2 AMP was associated with better PFS and a higher ORR for trastuzumab therapy. Furthermore, several reports attest to the association of ERBB2 AMP, as determined through copy number analysis using NGS, with more favourable prognosis in trastuzumab therapy [ 22 , 25 27 ]. Assessment of ERBB2 CNA via a targeted tumour sequencing test is advantageous for identifying patients likely to exhibit a favourable response to trastuzumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tmab monotherapy does not significantly inhibit ERK and S6 activity on OE33 cells [ 25 ]. Consistently, MET co-amplifications are significantly associated with worse outcomes, indicating resistance to anti-HER2 targeted therapy for HER2+ GC in a post hoc analysis of 327 samples from the JACOB trial [ 26 ]. Here, treatment of OE33 cells with Tmab, savolitinib, or their combination effectively suppressed the growth of colonies ( Figure 5 a) and the downstream molecules, AKT, ERK, and S6 ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 98%
“…Second, the reproducibility of HER2 CNV assessment may have been negatively influenced by the heterogeneity of the NGS assays. It should be also kept in mind that NGS may underestimate the HER2 CNV because of the stromal dilution as compared with standard morphologic assays such as ISH ( 25 ). Finally, a substantial proportion of patients with primary resistance did not display any PRESSING-HER2 alteration nor low HER2 CNV by tissue NGS.…”
Section: Discussionmentioning
confidence: 99%